2017
DOI: 10.7205/milmed-d-16-00105
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Help-Seeking Intentions in Operation Enduring Freedom and Operation Iraqi Freedom Veterans and Service Members

Abstract: This is one of the first studies to examine attitudes toward psychotherapy as contributing to help-seeking intentions of veterans and service members and results provide strong support for inclusion of this variable in future studies in addition to social support and stigma. Limitations of the study are discussed as well as suggestions for future research. It is our hope that findings from this study may inform administrators and providers regarding assessment, outreach, and program development for our country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
6
18
0
Order By: Relevance
“…This was to maintain confidentiality and privacy for veterans who may have felt self-conscious or stigmatized if others in the military were aware of their attendance. As noted earlier, this is a known deterrent to seeking help and engaging in therapeutic activity, especially among military and ex-military (Jain, et al, 2012;Porcari, et al, 2017) Participants gave informed consent after registering for the dancing program and prior to answering any of the questions on the three pre-program assessments. Participants in the program were assured that they did not need to consent to having this data collected in order to participate in the dance program.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was to maintain confidentiality and privacy for veterans who may have felt self-conscious or stigmatized if others in the military were aware of their attendance. As noted earlier, this is a known deterrent to seeking help and engaging in therapeutic activity, especially among military and ex-military (Jain, et al, 2012;Porcari, et al, 2017) Participants gave informed consent after registering for the dancing program and prior to answering any of the questions on the three pre-program assessments. Participants in the program were assured that they did not need to consent to having this data collected in order to participate in the dance program.…”
Section: Methods Participantsmentioning
confidence: 99%
“…We envisioned an experience that would allow for regular, routine, reintegration of body, mind, family, and community for those already under medical and psychotherapeutic treatment. The experience would have to be something that facilitated being part of a wider community, would involve physical activity and interactivity, could include family members and friends (Batten, et al, 2009;Fischer, Sherman, Han, & Owen, 2013;Hawkins, McQuire, Britt, & Linder, 2015;Porcari, et al, 2017), would be accessible to beginners but still engaging for the more advanced, would involve predictable patterns and movement, and would provide safety from intrusive memories, unpredictable behaviors and emotions, and the still-prevalent stigma associated with military and ex-military seeking mental health help (Khaylis, Polusny, Erbes, Gewirtz, & Rath, 2011;Hoge, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…8 Barriers to seeking or completing conventional therapies include concerns about the invasiveness of treatment, lack of emotional readiness for treatment, stigma associated with having a mental health condition, and logistical issues. 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…For example, Seal et al (2009), found in their study with 289,328 Iraq and Afghanistan veterans entering Veterans Affairs (VA) health care from 2002 to 2008, that mental health diagnoses increased substantially after the start of the Iraq war, especially among veterans younger than 25 years old. Yet, consistent with the general population, the prevalence of treatment-seeking for mental health problems is between 23 and 58 percent (Clement et al 2014;Henderson et al 2013;Ouimette et al 2011;Porcari et al 2017;Rosen et al 2011;Stecker et al 2007). Considering that, for the most part, both military personnel and veterans have access to a universal healthcare system, understanding what might increase or decrease the propensity to seek treatment for mental health problems among military veterans is an important area of investigation.…”
mentioning
confidence: 99%
“…Evidence for the first two factors of HBM are established in the literature investigating treatment-seeking for mental health among veterans. Symptom severity and greater impairment are consistently reported to be associated with seeking treatment for mental health problems among OIF/OEF veterans (DeViva et al 2016 ; Hines et al 2014 ; Porcari et al 2017 ; Rosen et al 2011 ). Evidence for the cost/benefit factor related to stigma and treatment-seeking described by the HBM has however, received inconsistent support, possibly due to methodological challenges (Sharp et al 2015 ).…”
mentioning
confidence: 99%